2010
DOI: 10.1111/j.1530-0277.2010.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Wake‐Promoting Basal Forebrain and Adenosinergic Mechanisms in Sleep‐Promoting Effects of Ethanol

Abstract: BACKGROUND Ethanol intake has significant impact on sleep. However, the cellular substrates responsible for sleep promotion following ethanol intake are unknown. The purine nucleoside, adenosine, is responsible for mediating many neuronal and behavioral responses to ethanol. Studies performed in cell cultures suggest that ethanol inhibits equilibrative nucleoside transporter 1 to block the reuptake of adenosine resulting in increased extracellular adenosine. Adenosine also has a pivotal role in sleep regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 42 publications
0
89
0
Order By: Relevance
“…[55][56][57][58][59] The recent studies by Thakkar and coworkers strongly suggest that alcohol-induced increase in adenosine in the basal forebrain and stimulation of A 1 receptors in the cholinergic neurons of the corticopetal basal forebrain arousal system is particularly involved in the acute somnogenic effects of alcohol. [60][61][62] First, they showed with in vivo microdialysis that local perfusion of alcohol elevates significantly the extracellular concentration of adenosine in the basal forebrain. 60 Second, systemic alcohol administration reduced the activity of cholinergic cells in the basal forebrain and the bilateral microinjection of an A 1 receptor antagonist in the same brain region significantly attenuated alcohol-induced sleep.…”
Section: Adenosine As a Mediator Of The Psychostimulant Effects Of Camentioning
confidence: 99%
See 1 more Smart Citation
“…[55][56][57][58][59] The recent studies by Thakkar and coworkers strongly suggest that alcohol-induced increase in adenosine in the basal forebrain and stimulation of A 1 receptors in the cholinergic neurons of the corticopetal basal forebrain arousal system is particularly involved in the acute somnogenic effects of alcohol. [60][61][62] First, they showed with in vivo microdialysis that local perfusion of alcohol elevates significantly the extracellular concentration of adenosine in the basal forebrain. 60 Second, systemic alcohol administration reduced the activity of cholinergic cells in the basal forebrain and the bilateral microinjection of an A 1 receptor antagonist in the same brain region significantly attenuated alcohol-induced sleep.…”
Section: Adenosine As a Mediator Of The Psychostimulant Effects Of Camentioning
confidence: 99%
“…60 Second, systemic alcohol administration reduced the activity of cholinergic cells in the basal forebrain and the bilateral microinjection of an A 1 receptor antagonist in the same brain region significantly attenuated alcohol-induced sleep. 61 In relation to anxiety, several studies have shown the involvement of A 1 receptors. A 1 receptor knockout mice display enhanced anxiety, 63 and the anxiogenic effects of caffeine have been generally attributed to blockade of A 1 receptors, although a role of A 2A receptors cannot be discarded.…”
Section: Adenosine As a Mediator Of The Psychostimulant Effects Of Camentioning
confidence: 99%
“…Neuronal activation is indicated by induction of c-Fos (Thakkar et al, 2010; Shiromani et al, 1992; Morgan and Curran, 1991; McKenna et al, 2009). Thus, activation of NAc was examined by monitoring c-Fos expression with immunohistochemistry (IH).…”
Section: Methodsmentioning
confidence: 99%
“…Rats were divided in four groups: ACSF+W, EtOH, NiC and NiC+EtOH. ACSF (500 nl/side) was bilaterally microinjected into the BF of ACSF+W and EtOH group, whereas nicotine [75 pmol (equivalent to 11 ng nicotine free base)/500 nl/side] was bilaterally microinjected into the BF of the NiC and NiC+EtOH groups as described previously (Thakkar et al, 2008a, 2010). In brief, the rat was gently swaddled in a towel.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study in rodents showed that ethanol promotes non-REM sleep but does not affect REM sleep. The somnogenic effect of ethanol is related to adenosine inhibition of wake-promoting neurons in the basal forebrain via A 1 R. Bilateral microinjections of the selective A 1 R antagonist DPCPX in this area reduce the effect of ethanol on non-REM sleep [113]. A study in which ethanol was administered to mice, either alone or in combination with selective AR agonists and antagonists, and animals were tested for anxiety in the elevated plus-maze, has indicated that activation of A 1 R also mediates the anxiolytic effect of ethanol [114].…”
Section: Effects Of Ethanolmentioning
confidence: 99%